2020
DOI: 10.1093/cercor/bhaa158
|View full text |Cite
|
Sign up to set email alerts
|

Partial Support for an Interaction Between a Polygenic Risk Score for Major Depressive Disorder and Prenatal Maternal Depressive Symptoms on Infant Right Amygdalar Volumes

Abstract: Psychiatric disease susceptibility partly originates prenatally and is shaped by an interplay of genetic and environmental risk factors. A recent study has provided preliminary evidence that an offspring polygenic risk score for major depressive disorder (PRS-MDD), based on European ancestry, interacts with prenatal maternal depressive symptoms (GxE) on neonatal right amygdalar (US and Asian cohort) and hippocampal volumes (Asian cohort). However, to date, this GxE interplay has only been addressed by one stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 80 publications
3
40
0
Order By: Relevance
“…We did not observe an interaction of PRS‐MDD with an early environmental risk factor, that is, prenatal maternal depressive symptoms, on dorsal striatal volumes. By contrast, such an interaction has been found for infant limbic volumes (i.e., amygdalar and hippocampal volumes; Acosta et al., 2020; Qiu et al., 2017). Striatal compared to limbic volumes show a higher heritability and are less influenced by unshared environmental factors (~20% vs. ~35%–50%; Blokland et al., 2012; Kremen et al., 2010).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We did not observe an interaction of PRS‐MDD with an early environmental risk factor, that is, prenatal maternal depressive symptoms, on dorsal striatal volumes. By contrast, such an interaction has been found for infant limbic volumes (i.e., amygdalar and hippocampal volumes; Acosta et al., 2020; Qiu et al., 2017). Striatal compared to limbic volumes show a higher heritability and are less influenced by unshared environmental factors (~20% vs. ~35%–50%; Blokland et al., 2012; Kremen et al., 2010).…”
Section: Discussionmentioning
confidence: 93%
“…There is growing evidence that PRS‐MDD predict MDD risk in children and adults, as a main effect and/or in interaction with environmental factors (Peyrot et al., 2014; Taylor et al., 2019). Recent studies suggested that PRS‐MDD shapes limbic brain (namely amygdalar and hippocampal) development as early as in the prenatal period, interacting with prenatal maternal depressive symptoms, an early environmental risk factor for child development (Acosta et al., 2020; Qiu et al., 2017). Evidence is mounting that psychiatric disease susceptibility can originate in early life stages (Kim, Bale, & Epperson, 2015; O'Donnell & Meaney, 2017; Rice et al., 2010), and might to some extent be mediated by altered offspring brain development (Acosta et al., 2019; Sandman, Buss, Head, & Davis, 2015; Wen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes and ages at scan are shown in Supplementary Table 1 . Fifty-two studies were completely cross-sectional and performed only one scan per each subject ( Hazlett et al, 2012 ; Deniz Can et al, 2013 ; Deoni et al, 2013 , 2015 ; Gao et al, 2013 ; O’Muircheartaigh et al, 2013 , 2014 ; Qiu et al, 2013a , 2015b ; Broekman et al, 2014 ; Dean et al, 2014b , c , 2017 , 2018a , b ; Grewen et al, 2014 ; Travis et al, 2014 ; Zhang et al, 2014 ; Donald et al, 2015 ; Langer et al, 2015 ; Ou et al, 2015 ; Poh et al, 2015 ; Spann et al, 2015a , b , 2020a , b ; Ferradal et al, 2016 , 2019 ; Li et al, 2016 ; Sethna et al, 2016 ; Adibpour et al, 2018 , 2020 ; Lugo-Candelas et al, 2018 ; Monnelly et al, 2018 ; Chen et al, 2019 ; Hernandez-Castillo et al, 2019 ; Lebenberg et al, 2019 ; Lehtola et al, 2019 ; Ong et al, 2019 ; Tuulari et al, 2019 ; Acosta et al, 2020a , b , 2021 ; Alexander et al, 2020 ; Bruchhage et al, 2020 ; Camacho et al, 2020 ; Dowe et al, 2020 ; Fenchel et al, 2020 ; Gale-Grant et al, 2020 ; Graham et al, 2020 ; Merhar et al, 2020 ; Merz et al, 2020 ). The remaining studies ( n = 34) were longitudinal and conducted serial scans on the same individuals ( Geng et al, 2012 , 2016 ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes and ages at scan are shown in Supplementary Table 1. Fifty-two studies were completely cross-sectional and performed only one scan per each subject (Hazlett et al, 2012;Deniz Can et al, 2013;Deoni et al, 2013Deoni et al, , 2015Gao et al, 2013;O'Muircheartaigh et al, , 2014Qiu et al, 2013aQiu et al, , 2015bBroekman et al, 2014;Dean et al, 2014bDean et al, ,c, 2017Dean et al, , 2018aGrewen et al, 2014;Travis et al, 2014;Zhang et al, 2014;Donald et al, 2015;Langer et al, 2015;Ou et al, 2015;Poh et al, 2015;Spann et al, 2015aSpann et al, ,b, 2020aFerradal et al, 2016Ferradal et al, , 2019Li et al, 2016;Sethna et al, 2016;Adibpour et al, 2018Adibpour et al, , 2020Lugo-Candelas et al, 2018;Monnelly et al, 2018;Chen et al, 2019;Hernandez-Castillo et al, 2019; Lebenberg et al, 2019;Lehtola et al, 2019;Ong et al, 2019;Tuulari et al, 2019;Acosta et al, 2020aAcosta et al, ,b, 2021Alexander et al, 2020;Bruchhage et al, 2020;Camacho et al, 2020;…”
Section: Study Characteristicsmentioning
confidence: 99%